Developing a Video Script for the Three Unique Chinese Temples as Tourism Destination in Palembang - Achmad Leofaragusta; Nurul Aryanti; Aisyah Shahab; Muhammad Sabari (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
This research was aimed at designing a video script to promote three Chinese temples in Palembang. In this study, the writers used the research and development (R&D) method. The writers conducted five steps of the R&D method: 1) Preliminary investigation; 2) Designing; 3) Realization/construction; 4) Testing, revising, and evaluation; 5) Implementation [6]. The writers implemented these steps by designing the product. The data were collected from documentation, observation and interview in the preliminary investigation step. In the designing step, the writers arranged the structure and content of the script and made it become the first draft as a realization step. In the testing, revising and evaluating step, the draft of the video script regarding the language, structure of sentences, and the content of the script was revised by several experts starting from tourism, linguistics, and script writing experts. In the last step, the writers made it become the final script. The script was written in English by using Celtx as the software for writing the script. The script described the uniqueness and the long history of three Chinese temples in Palembang. In addition, to design a script, the R&D method [6] was linked to the ten steps of writing a script: finding an idea, creating a plan, researching, selecting material, planning the message, arranging the structure, drafting the script, first draft and testing script, and final draft [7].